Preliminary Considerations on the Development of a Bicultural Trilingual Education Model for Deaf Children in the Tunisian Context - Nefaa, Aymen; Boutora, Leila; Gala, Nuria (Frontiers in Education, 2022)
Deaf educational methods have been the subject of controversy among advocates of the oralist and the bilingual approaches for centuries. Over the past decades, the bilingual-bicultural method has proved its effectiveness in facilitating formal school learning and downscaling a higher rate of illiteracy compared to the hearing population. The bilingual-bicultural model in Western countries is designed and implemented in predominantly monolingual contexts or multilingual contexts with a dominant majority language. It aims at providing deaf learners with a simultaneous dual access to the deaf and hearing cultures through sign language and the written form of the majority spoken language. The objective of this dual access is to create a balanced form of bilingualism which will reinforce literacy development. In the Western context, the relative proximity of the written and spoken forms of the majority language allows the written form to function as a means of access to the socio-cultural heritage of the hearing community and to develop a sufficient degree of autonomy in a world where literacy became crucial. The application of the Western bilingual-bicultural model may at first glance seem tempting to mitigate a significant rate of illiteracy affecting 98% of the deaf Tunisian population. However, the diglossic situation in Tunisia, and in the Maghreb countries in general, rests upon the existence of two linguistic forms exhibiting considerable linguistic differences. On one hand, the Tunisian Dialectal Arabic (TDA) is the spoken form, and is the vehicle for the Tunisian socio-cultural heritage transmission. On the other hand, the written form, Modern Standard Arabic (AMS), assumes the role of institutional and literacy language. This particular situation requires a specific educational framework different from the classical bilingual-bicultural approach. We hypothesize that without taking into account Tunisian Dialectal Arabic, learners will not access the Tunisian hearing culture. This situation will potentially hinder literacy development in Modern Standard Arabic. Our article puts forward a trilingual-bicultural educational model adapted to the Tunisian diglossic situation. It includes TSL, and written ADT, as representatives of the deaf and hearing cultures which will both contribute to a more fluid development in a third language, written MSA, as the literacy language.